Model phonon spectra of Cu₇SiS₅I and Ag₇SiS₅I crystals - Nebola, I.I.; Katanytsia, A.F.; Shteyfan, A.Ya.; Shkyrta, I.M.; Studenyak, I.P.; Timko, M.; Kopčanský, P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
In the context of superspatial symmetry, the crystal structures of the Cu₇SiS₅I and Ag₇SiS₅I superionic conductors have been analyzed. To calculate the phonon spectra, the model of FCC superlattice (8а, 8а, 0; 8а, 0, 8а; 0, 8а, 8а) in the metric of protocrystal (а, а, 0; а, 0, а; 0, а, а) has been developed. For the developed model, the general (3+3)-dimensional basis, the array of modulation vectors, and mass modulation functions have been presented. The model calculations of phonon spectra dispersion for Cu₇SiS₅I and Ag₇SiS₅I crystals in schemes with various partial occupation of crystallographic orbits by Cu(Ag) atoms have been performed. The dispersion dependences of phonon spectra for Cu₇SiS₅I and Ag₇SiS₅I crystals in the high-symmetric directions of the Brillouin zone have been presented. The genesis of phonon branches of vibrational spectra has been analyzed. У концепції надпросторової симетрії проаналізовано кристалічну структуру суперіонних провідників Cu₇SiS₅I та Ag₇SiS₅I. Для розрахунку фононних спектрів розроблено модель надґратки ГЦК (8а, 8а, 0; 8а, 0, 8а; 0, 8а, 8а) у метриці протокристала (а, а, 0; а, 0, а; 0, а, а). Для розробленої моделі представлено загальний (3+3)-вимірний базис, масив векторів модуляції та функції модуляції маси. Проведено модельні розрахунки дисперсії фононних спектрів для кристалів Cu₇SiS₅I та Ag₇SiS₅I у схемах з різним частковим заповненням кристалографічних орбіт атомами Cu(Ag). Наведено дисперсійні залежності фононних спектрів для кристалів Cu₇SiS₅I та Ag₇SiS₅I у високосиметричних напрямках зони Бриллюена. Проаналізовано походження фононних гілок коливних спектрів.